Negative Third-Party Reactions to Male and Female Victims of Rape: The Influence of Harm and Normativity Concerns. Issue 9 (May 2022) - Mulder, Eva; Bohner, Gerd
Male and female victims of sexual violence frequently experience secondary victimization in the form of victim blame and other negative reactions by their social surroundings. However, it remains unclear whether these negative reactions differ from each other, and what mechanisms underlie negative reactions toward victims. In one laboratory study ( N = 132) and one online study ( N = 421), the authors assessed participants' reactions to male and female victims, and whether different (moral) concerns underlay these reactions. The reactions addressed included positive and negative emotions, behavioral and characterological blame, explicit and implicit derogation, and two measures of distancing. It was hypothesized that male victimization would evoke different types of (negative) reactions compared with female victimization, and that normative concerns would predict a greater proportion of the variance of reactions to male victims than female victims. Multivariate analyses of variance (MANOVAs) were conducted to test whether reactions to male and female (non-)victims differed. Multiple regression analyses were conducted to test the influence of gender traditionality, homonegativity, as well as binding and individualizing moral values on participants' reactions. Results revealed that participants consistently reacted more negatively to victims than to nonvictims, and more so to male than to female targets. Binding values were a regular predictor of negative reactions to victims, whereas they predicted positive reactions to nonvictims. The hypothesis that different mechanisms underlie reactions to male versus female victims was not supported. The discussion addresses implications of this research for interventions targeting secondary victimization and for future research investigating social reactions to victims of sexual violence. It also addresses limitations of the current research and considerations of diversity.